2008
DOI: 10.3164/jcbn.2008004
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Biochemical Parameters in Streptozotocin-induced Diabetic Rats by Oral Administration of Extracts and Fractions of <i>Cephalotaxus sinensis</i>

Abstract: Summary Cephalotaxus sinensis (C. sinensis) large size, evergreen tree common in China and utilized for numerous effective pharmacological applications in Chinese traditional medicine. The hepato-renal effects of C. sinensis were evaluated in vivo using Streptozotocin (STZ)-induced diabetic rats as an tentative model. Animals were orally treated with 80% EtOH extract (aq.EE), H2O extract (WtE) and ethylacetate (EaF)/butanol fractions (BtF) of C. sinensis (200 mg/kg, b.w.) for 28 days whereas control received v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
8
34
2
Order By: Relevance
“…These results come in accordance with the previous findings (Abubakar et al, 2009) demonstrated that diabetes induction caused insignificant changes in serum levels of ALT, AST, urea and creatinine. In the contrary, the present findings also disagree with others (Saeed et al, 2008) demonstrated an increase in blood urea nitrogen and uric acid in STZ induced diabetic rats indicated kidney dysfunction.…”
Section: Tablecontrasting
confidence: 56%
See 1 more Smart Citation
“…These results come in accordance with the previous findings (Abubakar et al, 2009) demonstrated that diabetes induction caused insignificant changes in serum levels of ALT, AST, urea and creatinine. In the contrary, the present findings also disagree with others (Saeed et al, 2008) demonstrated an increase in blood urea nitrogen and uric acid in STZ induced diabetic rats indicated kidney dysfunction.…”
Section: Tablecontrasting
confidence: 56%
“…However, this difference perhaps attributed to different species, dose and experimental period. The increased activity of AST in STZ induced diabetic rats indicated liver dysfunction as reported before in rats (Saeed et al, 2008). Liver damage was observed after oral administration of aqueous extract of Nigella sativa (10 ml/kg of body weight for 14 consecutive days) in rats (Tennekoon et al, 1991) or in mice after oral administration of an aqueous extract of the Black cumin seeds in 4 different doses, 6, 9, 14 and 21 g/kg (Vahdati-Mashhadian et al, 2005).…”
Section: Tablementioning
confidence: 86%
“…One of the most sensitive and dramatic indicators of kidney injury is an increase in serum creatinine (52) . Conversely, pre-treatment with the extract signifi cantly reduced the creatinine level in CCL4 treated rats.…”
Section: Groupsmentioning
confidence: 99%
“…Animals were housed in poly ethylene cages at temperature [21][22][23][24][25] 0 C, 12 h light/dark cycle and relative air humidity 40-45%. Rats fed at libido with the standard food and tap water.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%